Organizational and Economic Mechanism of Managing Aviation Infrastructure for Ship Traffic along the Northern Sea Route - Tatyana A. Chernyak (Арктика и Север)
The development of new territories and international relations requires modernization and the formation of new approaches to managing the implementation of major federal projects. The most important federal project aimed at increasing the competitiveness of the country’s economy in the international arena is the project for the development of transit container transportation along the water area and the Northern Sea Route. Great expectations are associated with the creation of new international economic relations, built using a new transport artery, the communication along which is formed along the shortest route, taking into account the peculiarities of the structure of our planet. The implementation of the pro-ject has clear time limits on the stages of its implementation. In 2027, it is planned to start movement along the Northern Sea Route sea transit route (hereinafter referred to as the NSR), which unites the eastern and western extremities of the Eurasian continent in autonomous navigation. By this time, the entire infrastructure of vessel traffic along the NSR should be ready and equipped with the necessary means of communication. This article aims to develop a mechanism for managing the aviation infrastructure capable of meeting the needs for ensuring the continuity of ship traffic along the NSR. The author has systematized the necessary management methods and supplemented the elements of the management subject structure, necessary and sufficient for the timely execution of the organizational decisions planned by the federal program.